2020
DOI: 10.21037/jtd.2020.02.50
|View full text |Cite
|
Sign up to set email alerts
|

Active tuberculosis risk associated with malignancies: an 18-year retrospective cohort study in Korea

Abstract: Background: Active tuberculosis (TB) develops in approximately 10% of people with a latent tuberculosis infection (LTBI). TB guidelines recommend that LTBI screening and treatments target high-risk patients.Malignancies are not universally considered a high-risk factor for active TB. This study aimed to determine the degrees to which active TB risk was associated with various cancers in a Korean population. Methods: This study involved patients aged ≥20 years who were diagnosed with cancer at Ulsan University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 24 publications
0
40
0
2
Order By: Relevance
“…Another study conducted in Canada reported the increased risk of active TB (aHR = 11.20) after 19 years of follow-up [ 50 ]. One retrospective study which investigated the incidence and risk of clinically diagnosed TB and bacteriologically confirmed TB (BCTB) in LC patients found the BCTB IRR was 50.35 in comparison with control [ 51 ]. One retrospective study in Thailand followed up 18 years and found a cumulative incidence 1.15% for TB in LC patients [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted in Canada reported the increased risk of active TB (aHR = 11.20) after 19 years of follow-up [ 50 ]. One retrospective study which investigated the incidence and risk of clinically diagnosed TB and bacteriologically confirmed TB (BCTB) in LC patients found the BCTB IRR was 50.35 in comparison with control [ 51 ]. One retrospective study in Thailand followed up 18 years and found a cumulative incidence 1.15% for TB in LC patients [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, like COPD, the presence of several baseline chronic inflammatory diseases especially HIV and AIDS may increase the incidence of LC in TB patients, an issue that was not addressed [ 56 ]. On the other hand, previous studies stated that patients with other cancer including oesophageal cancer, pancreatic cancer, hematologic malignancy, and head and neck cancer faced a particularly high risk of developing TB [ 13 , 51 ]. Even histological types of LC, including SmCC and sarcoma, were strongly associated with TB [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer, oesophageal cancer, pancreatic cancer, hematologic malignancy, and head and neck cancer patients are at an increased risk of contracting TB. These patients with high-risk cancers should mainly be targeted for LTBI screening and treatment [1]. The compliance of TB preventive therapy in immunocompromised patients like people living with Human immunodeficiency virus (PLHIV) already on antiretroviral therapy has been demonstrated to be good [11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer may have impairments in cell-mediated immunity due to chemotherapy, either directly or indirectly. As a result, many people who have LTBI and cancer develop active tuberculosis [1]. We herein describe one such case report of a patient diagnosed and treated with malignancy, developing tuberculosis later.…”
Section: Introductionmentioning
confidence: 95%